A Novel Approach to Isolating Improved Industrial Interspecific Wine Yeasts Using Chromosomal Mutations as Potential Markers for Increased Fitness - Bellon, Jennifer R.; Ford, Christopher M.; Borneman, Anthony R.; Chambers, Paul J. (Frontiers in Microbiology, 2018)
Wine yeast breeding programs utilising interspecific hybridisation deliver cost-effective tools to winemakers looking to differentiate their wines through the development of new wine styles. The addition of a non-S. cerevisiae genome to a commercial wine yeast can generate novel phenotypes ranging from wine flavor and aroma diversity to improvements in targeted fermentation traits. In the current study we utilised a novel approach to screen isolates from an evolving population for increased fitness in a S. cerevisiae x S. uvarum interspecific hybrid previously generated to incorporate the targeted phenotype of lower volatile acidity production. Sequential grape-juice fermentations provided a selective environment from which to screen isolates. Chromosomal markers were used in a novel approach to identify isolates with potential increased fitness. A strain with increased fitness relative to its parents was isolated from an early timepoint in the evolving population, thereby minimising the risk of introducing collateral mutations and potentially undesirable phenotypes. The evolved strain retained the desirable fermentation trait of reduced volatile acidity production, along with other winemaking traits of importance while exhibiting improved fermentation kinetics.